Political investment in economic protection a note - Balisacan, Arsenio M. (1987)
This note presents some aspects of the neoclassical economy of economic protection. It develops a conceptual framework which focuses on the costs and benefits of investment in political influence to certain coalitions in the society and how the benefit-cost structure may affect the level of economic protection and the amount of what Bhagwati called "directly unproductive profit-seeking" activities.
Keywords: Political science -- Economic aspects; Investments -- Political aspects